Relationship of pre-operative pure tone audiometry and ossicullar discontinuity in chronic suppurative otitis media - Carrillo, Rayner Jose C.
Background: Pure tone audiometry (PTA) is routinely used to determine conductive and sensorineural hearing status. Ossicular discontinuity is ussually assessed intra-operatively. If ossicular discontinuity can be predetermined by pure tone audiometry, perhaps the operative procedure of choice and prognosis of hearing can also be anticipated. Objective: To determine the association of preoperative and air bone gap levels on the presence of gross ossicular discontinuity among patients with chronic suppurative otitis media (CSOM). Methods: Records of 276 patients with chronic otitis media 7 to 75 years of age undergoing their first operation for chronic otitis media were reviewed. Preoperative audiograms and operative records for tympanomastoidectomy were evaluated. The records came from 114 patients operated on by residents in training at Philippine General Hospital from June 1999 to October 2003 and 162 patients operated on by a single consultant otologist in Philippine General Hospital and Manila Doctors Hospital from June 1987 to July 2004. Association of preoperative and operative findings and pure tone audiogram on the presence of gross ossicular chain discontinuity was determined using univariate logistic regression analysis. Frequency specific air bone gaps (ABG) cut-off values were compared to the intra-operative assessment of OD and corresponding likelihood ratio for a positive test, LR(+), and likelihood ratio for a negative test, LR(-), were noted. Multiple logistic regression analysis was done to determine relationship of PTA results with OD adjusted for preoperative and operative findings. Results: The presence of persistent ear discharge (adjusted odds ratio of 3.0, 95% CI 1.4-6.7.), size of tympanic membrane perforation (in decile, as percent perforation, adjusted OR of 1.04, 95% CI of 0.89-1.22), presence of cholesteatoma (adjusted odds ratio 7.6, (95% CI 3.2-18.0) and granulation tissue (adjusted odds ratio 3.6, 95% CI 1.7-7.7), air-bone gap at 1 KHz (in decile dB, adjusted odds ratio of 1.47, 95% CI of 1.15-1.88) and type of hearing loss (adjusted odds ratio 2.02, 95% CI of 0.96-4.2) were associated with presence of gross ossicular discontinuity. Frequency specific air bone gap (ABG) cut-off values may detect ossicular discontinuity in chronic suppurative otitis media namely: 50 dB ABG at 1 KHz (LR(+) of 2.2, 95% CI 1.3-3.8), >30 dB ABG at 2 KHz (LR(+)of 3.2, 95% CI 1.8-5.7), and >40 dB ABG at 4 KHz (LR(+) of 2.2, 95% CI 1.4-3.5) is best associated with the presence of ossicular discontinuity in general. In CSOM with no cholesteatoma, the air bone gaps of 30 dB at 2 KHz (LR(+) 2.8, 95% CI 1.4-5.9) and >40 dB at 4 KHz (LT(+) 2.2, 95% CI 1.2-3.9) increased the probability of ossicular discontinuity from 33% to 75%. These findings suggested that ossicular exploration may not be necessary for the former while an evaluation of the ossicular chain maybe mandatory for the latter in the setting where cholesteatoma is not present or suspected. Narrow air-bone gap values at lower frequencies were determinants of absence of ossicular chain discontinuity while wide air-bone gap values at higher frequencies best described presence of gross ossicular chain discontinuity. Conlusion and recommendation: Persistent ear discharge, presence of cholesteatoma and granulation tissue, air-bone gap at 1 KHz and type of hearing loss were significant factors associated with ossicular discontinuity. Narrow air bone gaps at lower frequencies suggested absence of ossicular discontinuity. Wide air bone gaps at higher frequencies suggested presence of ossicular discontinuity. Based on the results, a management of CSOM was proposed such that simple tympanoplasty could be recommended to patients with small chance of OD as assessed by PTA, while a mandatory exploration of the ossicular chain with possible reconstruction were suggested on subjects with high chance of disruption as assessed by PTA. The presence of cholesteatoma would warrant an outright exploration of the ossicular chain. This algorithm can be followed and be verified by a standard criterion study.